Rhodanine composite fluorescence probes to detect pathological hallmarks in Alzheimer's disease models - Rai H.; Singh R.; Bharti P.S.; Kumar P.; Rai S.; Varma T.; Chauhan B.S.; Nilakhe A.S.; Debnath J.; Dhingra R.; Mishra V.N.; Gupta S.; Krishnamurthy S.; Yang J.; Garg P.; Srikrishna S.; Kumar S.; Modi G. (My University, 2025)
Amyloid fibrils and hyperphosphorylated tau tangles are widely acceptable histological and biochemical pathogenic markers in Alzheimer's Disease (AD). Detecting these markers at an early stage could be beneficial for differentiating AD from other neuronal anomalies. Herein, a series of rhodanine (acceptor) based dyes in conjugation with a coumarin or carbostyril (donor) were synthesized and tested their ability to detect these biomarkers. The lead probe 19 displayed staining affinity for Aβ fibrils and tau tangles with little or no interaction with abundant plasma protein (BSA). Minimal cytotoxicity, brain accessibility, biocompatibility, and fluorescence sustainability across physiological pHs rendering it suitable for in-vivo imaging. Dual staining of histological samples validated affinity of probe 19 for Aβ plaques and tau tangles in AD brain tissue specimens via immunofluorescence, ThT (aggregated Aβ specific dye), and Tau-1 (tau filament-specific dye). Moreover, live in-vivo fluorescence imaging in mice and ocular labeling of Aβ in AD Drosophila models extend the preclinical applicability of probe 19 for screening purposes. On behalf of the following data, we assume that probe 19 can successfully detect pathological AD biomarkers in investigational studies. © 2024 Elsevier B.V.